On the Connotative Nature of Floronyms in the Phraseological Units of the Russian and Uzbek Languages - Sobirzhanovna, Dustova Dildora (European Journal of Life Safety and Stability (2660-9630), 2022)
This curtain dissertation work is devoted to the modern and prospective problems of the language, that is the phareology and pharemiology units of the Russian and Uzbek languages. In this research work the metaphovical meanings of the floranimic words (the names of plants) which are in the Russian and Uzbek languages phaseologic and pjaremiologic lexical unis have been wudely studied by comparative ways.